• решите уравнение:
    1)-1,4(х-6)=7(4х+1,2)
    2)2,6(0,4х-1,4)=-3,9(1,2х-0,9)

Ответы 1

  • 1) -1,4(х - 6) = 7(4х + 1,2)- 1,4х + 8,4 = 28х + 8,4- 1,4х - 28х = 8,4 - 8,4- 29,4х = 0х = 0 : (- 29,4)х = 0Проверка: - 1,4(0 - 6) = 7(4 * 0 + 1,2)                  - 1,4 * (- 6) = 7 * 1,2                    8,4 = 8,42) 2,6(0,4х - 1,4) = - 3,9(1,2х - 0,9)1,04х - 3,64 = - 4,68х + 3,511,04х + 4,68х = 3,51 + 3,645,72х = 7,15х = 7,15 : 5,72х = 1,25  Проверка: 2,6(0,4 * 1,25 - 1,4) = - 3,9(1,2 * 1,25 - 0,9)                  2,6(0,5 - 1,4) = - 3,9(1,5 - 0,9)                  2,6 * (- 0,9) = - 3,9 * 0,6                  - 2,34 = - 2,34    
  • Добавить свой ответ

Еще вопросы

Войти через Google

или

Забыли пароль?

У меня нет аккаунта, я хочу Зарегистрироваться

How much to ban the user?
1 hour 1 day 100 years